Professores de matemática em formação e exercício profissional : entrelaçando interesses e olhares - Alves, Lourimara Farias Barros (2019)
This paper is a research on the training of Mathematics teachers developed within the Centro de Estudos Superiores de Balsas, of the Universidade do Estado do Maranhão – Brasil (CESBA-UEMA-Br). One of the motivations for this research is the situation there was in this course, where the gradual reduction in the number of students in classes and the suspension of the entrance exam for Mathematics Campus of Balsas for two consecutive years has caused noticeable discouragement in the teaching and students cadres of this campus that currently works with some classes with fewer than ten students. I developed a qualitative narrative mode research which aims to elucidate the relevant factors of institutional views, training and teaching practices that characterize the absence of elements for motivation training and teaching. I sought, therefore, to study and analyze effective personal, institutional, historical actions that can contribute to stimulating teacher training in Math in higher education and subsequent professional practice, in order to discuss both the implications of management, teaching, scientific practices and promoting factors of the undergraduates of interest in that practice. This were done with documentary and field research in which I analyze travel documents (projects, reports, minutes) and interviews (individual and semi-structured groups) with six managers, four teachers-trainers, twenty-eight academic course students (three veterans and twenty-five freshmen) and eleven graduated and eligible for professional practice, which are all the subjects of this research. Field notes resulted from research and their analysis was done through the prism of Textual Discourse Analysis by impregnation of the empirical data, readings intersecting concerning with the main question of the research. In arising from the textual analysis were recorded three axes namely: (i) Mishaps arising from preliminary examinations access to the university, (ii) Initial Teacher Training and (iii) Professional Practice and Postgraduate Teacher Training. The results show the importance of some of the many conditions that contribute to the proper training of Math teachers and affect those factors not only access to the Bachelor's Degree in itself, the existence of regular supply of places annually and also proactive beneficial actions by the Institution of Higher Education, attitudes of teachers-trainers course, creating future opportunities and the teaching value. Such actions can act decisively as enhancers to create a positive motivation environment for higher training period and the entry into the professional world. But the interviews reveal that there were also very negative effects of actions such as centrallydesigned order to suspend the entrance exams for two years without any prior discussion with the academic staff of CESBA. These actions were highly discouraging for this academic group in its three professional groups. This appears significantly in interviews and their analyses indicate that it is necessary to train teachers aiming to bridge the gap between university, community and school, which allows not only critical reflection on the feeling of overcoming the separation between the fields of training and teaching and not just worrying about the formative and educational sense of what is taught and learned. Nevertheless they also referred to a need for a place in dialogue impositions top-to-bottom guided orders less in academic deliberations and discussions with the academic community and more on the economy and on the basis of previous legal formulations. On the other hand, it proved insufficient communication and dialogue between those involved in the training process. The participants recognize and realize how important it is to establish between themselves a partnership relation seeking to win a training for the full exercise of a conscious citizenship.